Deletion of Lysophosphatidic Acid Receptor 3 (Lpar3) Disrupts Fine Local Balance of Progesterone and Estrogen Signaling in Mouse Uterus During Implantation. Issue 5 (1st November 2015) - Diao, Honglu; Li, Rong; El Zowalaty, Ahmed E.; Xiao, Shuo; Zhao, Fei; Dudley, Elizabeth A.; Ye, Xiaoqin
Abstract: Lpar3 encodes LPA3, the third G protein-coupled receptor for lysophosphatidic acid (LPA). Lpar3 −/− female mice had delayed embryo implantation. Their serum progesterone and estrogen levels were comparable with control on Gestation Day 3.5 (D3.5) at 1100 h. There was reduced cell proliferation in D3.5 and D4.5 Lpar3 −/− stroma. Progesterone receptor (PGR) disappeared from D4.5 Lpar3 +/+ uterine luminal epithelium (LE) but remained highly expressed in D4.5 Lpar3 −/− LE. Pgr and PGR- target genes but not estrogen receptor alpha (ERalpha [ Esr1 ]) or ESR target genes, were upregulated in D4.5 Lpar3 −/− LE. It was hypothesized that suppression of PGR activity in LE could restore on-time uterine receptivity in Lpar3 −/− mice. A low dose of RU486 (5 μg/mouse) given on D3.5 at 900 h rescued delayed implantation in all pregnant Lpar3 −/− females and significantly increased number of implantation sites compared to vehicle-treated pregnant Lpar3 −/− females detected on D4.5. E2 (25 ng/mouse) had a similar effect as 5 μg RU486 on embryo implantation in Lpar3 −/− females. However, when the ovaries were removed on late D2.5 to create an experimentally induced delayed implantation model, 25 ng E2 activated implantation in Lpar3 +/+ but not Lpar3 −/− females detected on D4.5. These results demonstrate that deletion of Lpar3 leads to an increased ratio of progesterone signaling/estrogen signaling that can be optimized by low doses of RU486 or E2 to restore on-time implantation in Lpar3 −/− females.